Succinic Semialdehyde Dehydrogenase Deficiency: Review of the Natural History Study. (November 2021) - Pearl, Phillip L.; DiBacco, Melissa L.; Papadelis, Christos; Opladen, Thomas; Hanson, Ellen; Roullet, Jean-Baptiste; Gibson, K. Michael
Objective: The SSADHD Natural History Study was initiated in 2019 to define the natural course and identify biomarkers correlating with severity. Methods: The study is conducted by 4 institutions: BCH (US clinical), WSU (bioanalytical core), USF (biostatistical core), and Heidelberg (iNTD), with support from the family advocacy group (SSADH Association). Recruitment goals were to study 20 patients on-site at BCH, 10 with iNTD, and 25 as a standard-of care cohort. Results: At this half-way point of this longitudinal study, 28 subjects have been recruited (57% female, mean 9 years, range 18 months–40 years). Epilepsy is present in half and increases in incidence and severity, as do psychiatric symptoms, in adolescence and adulthood. The average Full Scale IQ (FSIQ) was 53 (Verbal score of 56, Non Verbal score of 49), and half scored as having ASD. Although there was no correlation between gene variant and phenotypic severity, there were extreme cases of lowest functioning in one individual and highest in another that may have genotype-phenotype correlation. The most common EEG finding was mild background slowing with rare epileptiform activity, whereas high-density EEG and magnetoencephalography showed reduction in the gamma frequency band consistent with GABAergic dysfunction. MR spectroscopy showed elevations in the GABA/NAA ratio in all regions studied with no crossover between subjects and controls. Conclusions: The SSADH Natural History Study is providing a unique opportunity to study the complex pathophysiology longitudinally and derive electrophysiologic, neuroimaging, and laboratory data for correlation and to serve as biomarkers for clinical trials and prognostic assessments in this ultra-rare inherited disorder of GABA metabolism.